Beer, barley, livestock, milk: Who adopts agricultural innovations in rural Rajasthan? - Najjar, Dina; Baruah, Bipasha (Elsevier, 2024)
Research conducted in developing countries in the past 50 years generally suggests that most agricultural innovations (whether technological, social, or financial in nature) end up reinforcing existing socio-economic hierarchies based on gender and class. Most of these findings are drawn from the Green Revolution, which focused overwhelmingly on high-yielding varieties of rice, maize, and wheat, along with the introduction or expansion of irrigation and extension services and the use of fertilizers and pesticides. Less is known about how agricultural innovations involving other crops or livestock, especially if introduced in tandem, perform in alleviating poverty or reducing gender inequality. We conducted a study in three agricultural communities in rural Rajasthan, India to understand how the adoption of agricultural innovations for barley cultivation and livestock rearing are influenced by the gender, age, and class background of farmers, and whether such innovations can alleviate poverty and promote gender equality in rural settings. We found that although innovation adoption is influenced by gender, class and age (with gender exerting a stronger influence than class or age), poorer farmers and women can under certain circumstances benefit from agricultural innovations adopted initially by wealthier male farmers.